Developmental regulation of diacylglycerol acyltransferase family gene expression in tung tree tissues. - Heping Cao (Public Library of Science (PLoS), 2013)
Diacylglycerol acyltransferases (DGAT) catalyze the final and rate-limiting step of triacylglycerol (TAG) biosynthesis in eukaryotic organisms. DGAT genes have been identified in numerous organisms. Multiple isoforms of DGAT are present in eukaryotes. We previously cloned DGAT1 and DGAT2 genes of tung tree (Vernicia fordii), whose novel seed TAGs are useful in a wide range of industrial applications. The objective of this study was to understand the developmental regulation of DGAT family gene expression in tung tree. To this end, we first cloned a tung tree gene encoding DGAT3, a putatively soluble form of DGAT that possesses 11 completely conserved amino acid residues shared among 27 DGAT3s from 19 plant species. Unlike DGAT1 and DGAT2 subfamilies, DGAT3 is absent from animals. We then used TaqMan and SYBR Green quantitative real-time PCR, along with northern and western blotting, to study the expression patterns of the three DGAT genes in tung tree tissues. Expression results demonstrate that 1) all three isoforms of DGAT genes are expressed in developing seeds, leaves and flowers; 2) DGAT2 is the major DGAT mRNA in tung seeds, whose expression profile is well-coordinated with the oil profile in developing tung seeds; and 3) DGAT3 is the major form of DGAT mRNA in tung leaves, flowers and immature seeds prior to active tung oil biosynthesis. These results suggest that DGAT2 is probably the major TAG biosynthetic isoform in tung seeds and that DGAT3 gene likely plays a significant role in TAG metabolism in other tissues. Therefore, DGAT2 should be a primary target for tung oil engineering in transgenic organisms.